Shared funding of R&D in small and medium-sized innovative enterprises: the case of Chinese biomedical industry - Y. Sun (Ekonomika Nauki)
This study delves into the corporate governance challenges confronted by small and mediumsized innovative biomedical enterprises in the context of equity financing. Its objective is to provide valuable recommendations for the successful implementation of such financing. In order to address issues such as imperfect equity structure, inadequate financial audit systems, and low stability of the core team during equity financing, a range of improvement measures are proposed. These measures comprise optimizing internal management mechanisms, establishing an efficient R&D organizational structure, implementing practical incentive mechanisms for R&D enterprises focused on benefits, and enabling technical experts to actively engage in company ownership structures. Equity financing plays a vital role in resolving the difficulties faced by small and medium-sized innovative biomedical enterprises, particularly in fostering the development of innovative pharmaceutical products within the biomedical R&D field. Thus, it has a positive impact on effectively advancing China’s biomedical industry.”